Berberine attenuates adverse left ventricular remodeling and cardiac dysfunction after acute myocardial infarction in rats: Role of autophagy. (December 2014) - Zhang, Yao‐Jun; Yang, Shao‐Hua; Li, Ming‐Hui; Iqbal, Javaid; Bourantas, Christos V; Mi, Qiong‐Yu; Yu, Yi‐Hui; Li, Jing‐Jing; Zhao, Shu‐Li; Tian, Nai‐Liang; Chen, Shao‐Liang
Summary The present study aimed to test the hypothesis that berberine, a plant‐derived anti‐oxidant, attenuates adverse left ventricular remodelling and improves cardiac function in a rat model of myocardial infarction (MI). Furthermore, the potential mechanisms that mediated the cardioprotective actions of berberine, in particular the effect on autophagy, were also investigated. Acute MI was induced by ligating the left anterior descending coronary artery of Sprague‐Dawley rats. Cardiac function was assessed by transthoracic echocardiography. The protein activity/levels of autophagy related to signalling pathways (e.g. LC‐3B, Beclin‐1) were measured in myocardial tissue by immunohistochemical staining and western blot. Four weeks after MI, berberine significantly prevented cardiac dysfunction and adverse cardiac remodelling. MI rats treated with low dose berberine (10 mg/kg per day) showed higher left ventricular ejection fraction and fractional shortening than those treated with high‐dose berberine (50 mg/kg per day). Both doses reduced interstitial fibrosis and post‐MI adverse cardiac remodelling. The cardioprotective action of berberine was associated with increased LC‐3B II and Beclin‐1 expressions. Furthermore, cardioprotection with berberine was potentially related to p38 MAPK inhibition and phospho‐Akt activation. The present in vivo study showed that berberine is effective in promoting autophagy, and subsequently attenuating left ventricular remodelling and cardiac dysfunction after MI. The potential underlying mechanism is augmentation of autophagy through inhibition of p38 MAPK and activation of phospho‐Akt signalling pathways.